Magnesium ion-based gel polymer electrolytes: ionic conduction and infrared spectroscopy studies - Zainol, N.H.; Samin, S.M.; Othman, L.; Isa, K.B.M.; Chong, W.G.; Osman, Zurina (Electrochemical Science Group, 2013)
The gel polymer electrolyte (GPE) films based on polymethylmethacrylate (PMMA) containing the mixture of ethylene carbonate (EC) and propylene carbonate (PC) as a plasticizing solvent and various concentrations of magnesium triflate or Mg(CF3SO3)(2) salt have been prepared using the solution casting technique. The maximum room temperature ionic conductivity of 1.27 x 10(-3) S cm(-1) was obtained from the GPE film containing 20 wt. of Mg(CF3SO3)(2) salt. The conductivity-temperature studies of the GPE films follow the Arrhenius behavior with activation energy for ionic conduction are determined to be 0.18 - 0.26 eV. The transport number of magnesium ions in the GPEs was evaluated using the combination of a. c. impedance spectroscopy and d.c. polarization techniques. Fourier Transform Infrared Spectroscopy (FTIR) studies confirmed the increased in conductivity is due to increase of free ions and decrease in ion aggregates.